2023
DOI: 10.1177/23779608231196847
|View full text |Cite
|
Sign up to set email alerts
|

The Impact and Issues of Artificial Intelligence in Nursing Science and Healthcare Settings

Aprianto Daniel Pailaha

Abstract: Research and development of artificial intelligence (AI)-based technologies systems in healthcare has increased over the past decade, highlighting the strong potential of AI to improve the quality of nursing care. To meet the new demands for nursing care, it is necessary that AI be integrated into nursing science and healthcare setting, especially in nursing care. The current challenge is to transform this expanded set of technology into clinical benefits for patients, through more advanced, accurate, practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…These positive effects underscore the advantages and the pressing need for integrating AI technology systems in healthcare, with the aim of optimizing healthcare services for greater efficiency and effectiveness. 22 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These positive effects underscore the advantages and the pressing need for integrating AI technology systems in healthcare, with the aim of optimizing healthcare services for greater efficiency and effectiveness. 22 …”
Section: Resultsmentioning
confidence: 99%
“… 49 , 50 The review results showed that AI could be incorporated into EHR in terms of recording, organizing, and managing EHR data for optimal use, reducing time and effort, and increasing the quality of care. 22 For instance, one of the examples was the implementation of a voice-based AI system that provided real-time assistance for medical record input during the triage process in the emergency department. This system was trained on speech-to-text data and could reduce the triage time and improve the efficiency of emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…[24] To date, little AI in healthcare research has considered real-world scenarios or real-world effect on outcomes. [25] Uses of AI in nursing span from virtual assistants to patient monitoring and predictive modeling. [26] AI can also contribute by helping to streamline workflows and analyze vast amounts of data for evidence-based recommendations, helping nurses make more informed decisions about patient care.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing extensive datasets, ML-driven analytics provides insights that can identify health risks, refine diagnoses and treatments, and prevent adverse health events (Chilla, 2023). This technology is increasingly used in nursing for patient monitoring, chronic disease management, and emergency preparedness (Hwang et al, 2022;Pailaha, 2023). These developments highlight the significant impact of ML-driven predictive analytics on health care and its potential to revolutionize nursing practice.…”
Section: Machine Learningmentioning
confidence: 99%